(untitled) (LEARNing Landscapes, 2018)
By embedding narrative theory within the practice of storied forms, there can be pedagogical movement from difficulty to insight. This piece explores scholarly personal narrative as a creative and critical method for attaining academic understanding. The ideas of three narrative scholars (Nash, Fowler, and Luce-Kapler) surface within two writing forms—a letter and a poem. The author playfully reports on the powerful processes that are engaged when shared creative story forms become part of teaching, learning, and writing.